Systemic immune-inflammation index: Unveiling the diagnostic potential in ulcerative colitis through a comprehensive systematic review and meta-analysis - Anas Elgenidy; Omar Alomari; Tasbih Emad; Sara K. Kamal; Islam E. Al Ghanam; Aya Sherif; Mohammed Al-mahdi Al-kurdi; Abdallah A. Helal; Yusof Mohamed Omar; Mohamed Rafiek Ramadan (Gastroenterology & Endoscopy)
Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease with unpredictable colon and rectum inflammation episodes. Evaluating disease activity is essential for effective management. The systemic immune-inflammation index (SII) is a potential biomarker for assessing inflammation and disease severity in UC. This meta-analysis aims to comprehensively assess the utility of SII in UC by analyzing its association with disease activity. Methods: PubMed, Scopus, Embase, Cochrane, and Web of Science databases have been searched for relevant studies OpenMetaAnalyst software were utilized in the analysis. Furthermore, we conducted a diagnostic test accuracy (DTA) analysis using Meta-Disc version 2.0 software, employing a univariate model to assess the sensitivity, specificity, and predictive value of SII. Results: We included seven retrospective studies comprising 1127 UC patients and 686 healthy controls. Our analysis revealed a significantly higher SII in UC patients compared to healthy controls (mean difference: −620.00, 95 ​% CI -1337.08 – 97.07), indicating its potential as a diagnostic marker. SII was also significantly lower in UC patients in remission compared to those with active disease (mean difference: −521.71, 95 ​% CI -962.92 to −80.50), suggesting its role in monitoring disease activity. The DTA analysis demonstrated a pooled sensitivity of 0.622 and specificity of 0.805 for SII in predicting UC activity, with a diagnostic odds ratio of 6.773. Conclusion: Our meta-analysis reveals that the SII holds significant promise as a non-invasive marker for assessing the activity and severity of UC. The findings demonstrate that SII is significantly lower in healthy controls compared to UC patients and lower in patients in remission compared to those with active disease.